Impact of craniocervical junction abnormality on vertebral artery hemodynamics: based on computational fluid dynamics analysis - Zhang, Zeyuan; Ai, Xin; Xu, Yuanzhi; Wang, Yuqiang; Zhang, Shuhao; Zhao, Yao; Zhou, Ruifang; Tang, Rui; Wang, Limin; Liu, Yilin (Frontiers in Neurology, 2024)
Background and purpose A three-dimensional reconstruction and data analysis of the vertebral artery (VA) with craniocervical junction abnormality (CJA) was performed by computational fluid dynamics (CFD) based on images to assess the impact of CJA on vertebral artery hemodynamics. Methods Retrospective analysis of combined head and neck computed tomography angiography (CTA) images of 60 patients with CJA and 60 normal patients admitted to our department from January 2018 to June 2022. The VA was reconstructed in three dimensions using CFD-related software, and the results were visualized to derive vertebral artery lumen diameter (D), peak systolic velocity (PSV), mean blood flow velocity (MV), wall pressure (P), wall shear stress (WSS), normalized WSS (NWSS), etc. Statistical analysis was used to analyze whether the data related to hemodynamics in the CJA group and the control group were statistically significant. Results The lumen diameter of the vertebral artery in the CJA group were less than the control group, and the difference was statistically significant (3.354 ± 0.562 vs. 3.744 ± 0.520, p < 0.05); the PSV, MV, P, WSS, and NWSS of the CJA group were increased compared with the control group, and the difference was statistically significant (1.235 ± 0.182 vs. 1.104 ± 0.145, 0.339 ± 0.063 vs. 0.307 ± 0.042, 24576.980 ± 7095.836 vs. 20824.281 ± 6718.438, 34.863 ± 6.816 vs. 31.080 ± 5.438, 0.272 ± 0.075 vs. 0.237 ± 0.067, p < 0.05). Conclusion In the complex CJA, the possibility of hemodynamic variation in the VAs is higher than in the normal population. The hemodynamic aspects of the vertebral artery in patients with CJA, such as diameter, flow velocity, flow, wall pressure and shear force, differ from those in the normal population and may lead to the occurrence of clinical symptoms, such as dizziness, so preoperative examinations such as combined head and neck CTA should be performed to clarify the vascular abnormalities.